2013
DOI: 10.1371/journal.pone.0056558
|View full text |Cite
|
Sign up to set email alerts
|

The Deinococcus radiodurans DR1245 Protein, a DdrB Partner Homologous to YbjN Proteins and Reminiscent of Type III Secretion System Chaperones

Abstract: The bacterium Deinococcus radiodurans exhibits an extreme resistance to ionizing radiation. A small subset of Deinococcus genus-specific genes were shown to be up-regulated upon exposure to ionizing radiation and to play a role in genome reconstitution. These genes include an SSB-like protein called DdrB. Here, we identified a novel protein encoded by the dr1245 gene as an interacting partner of DdrB. A strain devoid of the DR1245 protein is impaired in growth, exhibiting a generation time approximately threef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Of the eight genes, three have homologs identified in all three domains of life, and all eight have homologs in eukaryotes. In no instance has the function of one of these homologs been described in detail, although some hints about YbjN, YebC, YejH, and YbgI functions have appeared (76,77,87,88). In several cases, we provide here the first phenotype described for cells lacking the functions of these genes.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Of the eight genes, three have homologs identified in all three domains of life, and all eight have homologs in eukaryotes. In no instance has the function of one of these homologs been described in detail, although some hints about YbjN, YebC, YejH, and YbgI functions have appeared (76,77,87,88). In several cases, we provide here the first phenotype described for cells lacking the functions of these genes.…”
Section: Discussionmentioning
confidence: 80%
“…At least one of the genes of unknown function may also be linked to the oxidative damage response. The ybjN gene encodes a protein with structural homology to the DR1245 protein of Deinococcus radiodurans and type III secretion system chaperones (87). Overexpression of ybjN leads to induction of the SOS response (88).…”
Section: Tablementioning
confidence: 99%
“…Recently, a novel protein encoded by the dr1245 gene was identified, which may have chaperon activity toward DdrB and possibly other substrates. Studies showed that a Δdr1245 strain is impaired in growth, but radioresistance is not affected (Norais et al 2013).…”
Section: Proteins Involved In Genome Preservation and Dna Repair Mechmentioning
confidence: 99%
“…The plasmids used are listed in Table S2. Genomic DNA was extracted from D. deserti and D. radiodurans (Norais et al, 2013) as described. To construct plasmids, PCR products were generally obtained using primers including restriction sites, and cloned in pCR4Blunt-TOPO prior to recloning in the desired vectors.…”
mentioning
confidence: 99%
“…Cell pellets from 20 ml of exponentially growing D. radiodurans cultures (OD 650 of 0.3-0.4) were obtained by centrifugation and resuspended in 150 ml of SSC1X (150 mM NaCl, 15 mM trisodium citrate, buffered at pH 7). The protein extract was prepared as previously described (Bouthier de la Tour et al, 2013). Samples of 5 mg of proteins were submitted to electrophoresis in a 12 % SDS-polyacrylamide gel.…”
mentioning
confidence: 99%